Edvard Griegs Jugendwerke im Spiegel seiner Leipziger Studienjahre - Dinslage, Patrick (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1996)
Edward Grieg, no more than 15 years of age, in October 1858 commenced his studies at the Leipzig conservatoire. Just four short piano pieces he had composed up to then. The musical language and formal structure of these pieces was formed along the outlines of the sort of music he had encountered at his home – his parents’ social life being that of a 19th century European ”salon” –, in the rich concert life of Bergen as well as through the facilities of a well developed system of lending libraries. One year later, in 1859, Grieg’s collection of original compositions had already grown to 23 piano pieces. This group, known as 23 smaastykker (EG 104) has recently been published in facsimile in volume 20 of the complete edition of Grieg’s works. There also the Tre klaverstykker (EG 105), composed at Leipzig in April 1860, have first been published. In 1861 Grieg composed Drei Phantasiestücke, compositions which he played in April 1862 as part of his final examinations at the Leipzig conservatoire and which were published – supplemented by a Mazurka and entitled Vier Stücke für das Pianoforte - by Musikverlag Peters at Leipzig in 1863/64 as his op. 1.